2016
DOI: 10.1097/coh.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Promise and pitfalls of pre-exposure prophylaxis for female sex workers

Abstract: For those FSWs who are unable to mitigate their HIV risk, PrEP, if adequately supported and integrated with combination prevention, may empower them to remain HIV-free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…Psychological empowerment might overcome the adverse effects of stigma and exclusion among FSWs (41). In line with another study (13), FSWs in this study also pointed towards stigmatizing the health care system. Easy accessibility at pharmacies or involvement of CBOs or grass root workers from health system for dispensing was preferred and an aversion for health care provider mediated oral PrEP emerged.…”
Section: 2) Preserving Beauty / Female Physical Attributes: Concernsupporting
confidence: 90%
“…Psychological empowerment might overcome the adverse effects of stigma and exclusion among FSWs (41). In line with another study (13), FSWs in this study also pointed towards stigmatizing the health care system. Easy accessibility at pharmacies or involvement of CBOs or grass root workers from health system for dispensing was preferred and an aversion for health care provider mediated oral PrEP emerged.…”
Section: 2) Preserving Beauty / Female Physical Attributes: Concernsupporting
confidence: 90%
“…Several studies related to PrEP and SRH needs of FSWs showed as well that combination prevention approaches are necessary. First, as pointed by a study in Zimbabwe,36 women need to perceive the risk of getting infected by HIV and to be able to access health services in order to take PrEP daily. Second, as shown by Dhana et al 37 in a systematic review, there is a lack of coordination between SRH and HIV services dedicated to FSWs in Africa when they are two distinct services; HIV services delivery models should integrate SRH services.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts and Mathews reiterated the importance of structural interventions along with biomedical and behavioral interventions for HIV prevention [ 21 ]. A study by Cowan and Delaney-Moretlwe focusing on female sex workers, found that structural issues such as stigma from medical professionals, poor social support, and fear of authorities and clients were major barriers to uptake, in addition to risk perception [ 22 ]. Ware et al found that social factors such as supportive relationships with family and sexual partners can improve PrEP uptake and adherence [ 23 ]; these findings are similar to those of studies on antiretroviral adherence for HIV-positive individuals [ 24 ].…”
Section: Introductionmentioning
confidence: 99%